Development of a Blast System and Chatbot for Information Dissemination in the IPI Community (Ibu Pembelajar Indonesia) Using the WhatsApp-Web.js Library: Pengembangan Sistem Blast dan Chatbot untuk Penyebaran Informasi di Komunitas IPI (Ibu Pembelajar Indonesia) dengan Menggunakan Library WhatsApp-Web.js - Rosyad, Alwan Jauza; Utami, Ardhini Warih (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2024)
The research focuses on the development of a blast system and chatbot for disseminating information within the IPI (Ibu Pembelajar Indonesia) Community using the Whatsapp-web.js library. The main objective of this research is to address the limitation of the maximum number of members in a WhatsApp group, which is only 1,024 members, and to disseminate information in a community that has more than 4,000 members. The Rapid Application Development (RAD) method is used in the development of this system, which includes the stages of requirement planning, design, rapid construction, and cutover. The results of the study indicate that the blast system enables admins to disseminate information en masse to all members without having to select numbers one by one, while the chatbot provides automatic interaction and real-time responses to community members. The developed system has proven to be effective in disseminating information quickly and accurately, reducing manual workload, and minimizing the potential for communication errors. Moreover, the implemented chatbot technology has successfully enhanced member engagement and satisfaction through more dynamic interactions and content personalization based on usage data analysis. Nonetheless, this research suggests the development of additional features, enhancement of data security, and training and socialization to ensure optimal system utilization. Further research is needed to evaluate the long-term impact of using this system and to test its scalability in other communities or organizations with complex communication needs.